2016
DOI: 10.1016/j.atmosenv.2015.10.058
|View full text |Cite
|
Sign up to set email alerts
|

Trend estimates of AERONET-observed and model-simulated AOTs between 1993 and 2013

Abstract: Recently, temporal changes in Aerosol Optical Thickness (AOT) have been investigated based on model simulations, satellite and ground-based observations. Most AOT trend studies used monthly or annual arithmetic means that discard details of the generally right-skewed AOT distributions. Potentially, such results can be biased by extreme values (including outliers). This study additionally uses percentiles (i.e., the lowest 5%, 25%, 50%, 75% and 95% of the monthly cumulative distributions fitted to Aerosol Robot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 96 publications
2
28
0
Order By: Relevance
“…Trends in aerosol loading over the period 1995-2009 were recently compiled by Yoon et al (2016) at 15 AERONET stations. They showed that fine-mode anthropogenic aerosol is decreasing over those countries with strict environmental regulations, and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…Trends in aerosol loading over the period 1995-2009 were recently compiled by Yoon et al (2016) at 15 AERONET stations. They showed that fine-mode anthropogenic aerosol is decreasing over those countries with strict environmental regulations, and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, different aerosol types originate from several sources with diverse physical and optical properties, and from various atmospheric impacts [6][7][8][9][10]. Each aerosol type has a different climatic effect due to their size and absorptive and scattering nature, such as dust particles having large sizes and sulfate aerosols having a scattering nature, whereas nitrate particles with small sizes have absorbing tendencies [7,8,[11][12][13][14][15][16]. Consequently, long-term measurements of aerosol optical properties and aerosol types at a large scale are necessary to interpret the aerosol climatic effect [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The association of human activity with the presence of tropospheric aerosols is well established from both ground-based (Jimenez et al 2009;Yoon et al 2016) and space-based observations (Streets et al 2013;Yoon et al 2014;He et al 2016;McLinden et al 2016). Yet, quantification of the RF of climate due to tropospheric aerosols continues to pose a scientific challenge due to the inability to precisely define numerical values of both the direct modulation of RF by anthropogenic aerosols (Myhre 2009;Kahn 2012;Bond et al 2013) and the changes in RF driven by the effect of aerosols on clouds (Morgan et al 2006;Carslaw et al 2013).…”
Section: Aerosolsmentioning
confidence: 99%